he guitar as a poetic symbol in Dominican bachata (Orkopata. Revista de Lingüística, Literatura y Arte, 2025)
Bachata is a cultural and musical phenomenon that has undergone a significant transformation, evolving from a marginal genre to a symbol of national identity in the Dominican Republic. The objective of this research is to explore the meaning of the guitar and its role as a lyrical subject in the semantic construction of bachata. The study adopts a qualitative approach with a hermeneutic design. The main techniques include semiotic analysis of musical compositions and the use of an analytical guide to identify the function of musical time and its relationship to poetic content. A total of 24 representative bachata songs from various decades (1960–2020) were selected. The findings indicate that the guitar strings act as a lyrical subject capable of reinforcing the emotional message of the song. On average, 30% of the composition time is dedicated to instrumental segments where the guitar takes center stage. Moreover, the presence of the guitar is closely linked to the transmission of ancestral lyricism, reinforcing the identity and character of bachata. The study concludes that the guitar plays an essential role in bachata’s lyrical narrative, not only as an accompaniment but as a bearer of meaning that enriches poetic expression. This research highlights the cultural dimension of bachata, showing how the guitar consolidates a Caribbean musical language and opens pathways for exploring the relationship between music and meaning in Caribbean art.
Keywords: artistic creation; musical instruments; popular music; poetry